Pengaruh Gender Diversity, Kompensasi Bonus, dan Komisaris Independen terhadap Manajemen Laba : (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2018-2022) (International Forum of Researchers and Lecturers, 2025)
The purpose of this study is to determine the effect of gender diversity, stock bonus compensation, and financial expertise of independent commissioners on earnings management in manufacturing companies in Indonesia for the period 2018-2022. This study uses secondary data obtained through the annual financial reports of manufacturing companies listed on the IDX for the period 2018-2022. This study is a quantitative study with sampling using the purposive sampling method and obtaining 135 research sample data. The analysis method used is multiple linear regression analysis using SPSS software version 27. The results of this study indicate that the Board of Directors Gender Diversity variable has a significant positive effect on earnings management. The Stock Bonus Compensation variable has a significant negative effect on earnings management. Meanwhile, the Independent Commissioner Financial Expertise variable has a positive but insignificant effect on earnings management.